Updated Genome Assembly and Annotation for Metrosideros polymorpha, an Emerging Model Tree Species of Ecological Divergence. Issue 11 (1st November 2019) - Izuno, Ayako; Wicker, Thomas; Hatakeyama, Masaomi; Copetti, Dario; Shimizu, Kentaro K
Abstract: Accurate feature annotation as well as assembly contiguity are important requisites of a modern genome assembly. They allow large-scale comparison of genomes across and within species and identification of polymorphisms, leading evolutionary and functional studies. We report an updated genome resource for Metrosideros polymorpha, the most dominant tree species in the Hawaiian native forests and a unique example of rapid and remarkable ecological diversification of woody species. Ninety-one percent of the bases in the sequence assembly (304 Mb) were organized into 11 pseudo-molecules, which would represent the chromosome structure of the species assuming the synteny to a close relative Eucalyptus . Our complementary approach using manual annotation and automated pipelines identified 11.30% of the assembly to be transposable elements, in contrast to 4.1% in previous automated annotation. By increasing transcript and protein sequence data, we predicted 27, 620 gene models with high concordance from the supplied evidence. We believe that this assembly, improved for contiguity, and annotation will be valuable for future evolutionary studies of M. polymorpha and closely related species, facilitating the isolation of specific genes and the investigation of genome-wide polymorphisms associated with ecological divergence.